Effects of UVC Irradiation on Growth and Apoptosis of Scedosporium apiospermum and Lomentospora prolificans - Muangkaew, Watcharamat; Suwanmanee, San; Singkum, Pantira; Pumeesat, Potjaman; Luplertlop, Natthanej (Interdisciplinary Perspectives on Infectious Diseases, 2018)
Scedosporium apiospermum and Lomentospora prolificans are important fungal species isolated from immunocompromised patients. Previous studies have demonstrated that these filamentous fungi exist as saprophytes in the soil and showed the highest minimum inhibitory concentration to several drugs. We aimed to examine how UVC affects the S. apiospermum and L. prolificans by investigating the role of UVC on growth, induction of apoptosis by ethidium bromide (EB)/acridine orange (AO) staining, and transcriptomic study of caspase recruitment domain family, member 9 (CARD-9) gene. Our studies showed that 15 minutes of exposure to UVC light effectively increased reduction in both organisms and caused changes in colony morphology, color, and hyphal growth pattern. After 15 min of UVC irradiation, apoptotic cells were quantitated by EB/AO staining, and the percentage of apoptosis was 96.06% in S. apiospermum and 28.30% in L. prolificans. CARD-9 gene expression results confirmed that apoptosis was induced in S. apiospermum and L. prolificans after UVC treatment and that S. apiospermum showed a higher expression of apoptosis signaling than L. prolificans. Our study explored the effects of UVC in the inactivation of S. apiospermum and L. prolificans. We hope that our data is useful to other researchers in future studies.